Evaluation of first and second rice cultivation based on diazinon pesticide concentration in water and soil of paddy fields of Mazandaran province - Shina Ansari Hamedani; Reza Arjmandi; Saeed Motessadi Zarandi; Mohammad Ali Baghestani; Reza Azizinezhad (علوم محیطی)
Introduction: Consumption of organophosphorus pesticides in agriculture causes many environmental problems. Water and soil pollution and disruption of the balance of natural ecosystems, the emergence of new pests and diseases, the presence of pesticide residues in agricultural products and the resulting health effects have made the consumption management of organic phosphorus pesticides an unavoidable necessity. Despite the low per capita consumption of pesticides in the country on a global scale, the unfavorable use of organophosphorus pesticides in some parts of the country, including the Northern provinces and the resulting pollution, is one of the most important environmental issues in the country. In this study, according to the EIQ (Environmental Impact Quotient), diazinon pesticide was evaluated as hazardous to the environment of the study area due to its widespread use against Chilo suppressalis in water and soil of paddy fields.Material and methods: Detection of diazinon pesticide in water and soil of paddy fields in Mazandaran province was done by determining fixed stations for sampling in accordance with spraying paddy fields. A total of 50 soil and water samples were gathered for the first cultivation and 30 soil and water samples were gathered for the second cultivation and were measured by Gas Chromatography after being transferred to the laboratory. Sampling was done from late June to mid-August for the first cultivation, and from the first week of September to late October for the second cultivation of rice. Sampling was done in three seasons: spring, summer (before transplanting or during harvest) and autumn (for the second rice cultivation).Results and discussion:  The results of measuring the target pesticide show a significant difference in the amount of diazinon in the water of the first cultivation compared to the second cultivation and the soil of the first cultivation compared to the second cultivation. Also, the average of diazinon in the water samples of the second cultivation was 7.8 times higher compared to the first cultivation and 1.66 times higher in the soil samples of the second cultivation compared to the first cultivation, which indicates high and alarming amounts of diazinon in the second rice cultivation. Stability and solubility of diazinon, as well as the environmental conditions of Mazandaran province, especially the high groundwater level, extend the life of this pesticide and consequently cause serious environmental hazards.Conclusion:  Sustainable use of cultivated lands with a focus on improving production efficiency and increasing crop efficiency, creating a strategic center and a single regulator in the country to manage pesticide consumption, develop general and specialized training for groups of stakeholders in the production, supply and consumption of pesticides, registration and application of pesticides based on environmental impact factor, gradual removal and replacement of high-risk pesticide diazinon and the use of new methods and technologies to deal with important pests of rice are among the most important things that should be considered as strategies and executive policies resulting from research.